Substitution risk and continuing training behaviour in the digital shift : what are the gender-specific differences? - Seegers, Marco [Verfasser] (My University, 2020)
"Professional knowledge is ageing ever more quickly in the course of the digital shift, and continuing vocational training measures are becoming increasingly significant in terms of preparing the labour force for new and/or altered task requirements. The extent to which occupations typically exercised by men are affected differently to occupations in which women are in the majority remains unclear at present. This article conducts an investigation at the level of occupational groups in order to discover whether there is any evidence of a gender-specific risk of being affected by digital substitution processes and whether the previous continuing training behaviour displayed by the labour force has been adapted to digital structural change." (Authors's abstract; BIBB-Doku)
Keywords: G 2.3 Wandel von Arbeit & Wirtschaft; S 1.5 Weiterbildung; Digitalisierung; Tätigkeitswandel; Berufliche Weiterbildung; Weiterbildungsverhalten; Substitution; Risiko; Geschlechtsspezifische Faktoren; Männerberuf; Frauenberuf